Matrix metalloproteinase‐1‐mediated mesenchymal stem cell tumor tropism is dependent on crosstalk with stromal derived growth factor 1/C‐X‐C chemokine receptor 4 axis. Issue 10 (30th June 2014) - Ho, Ivy A. W.; Yulyana, Yulyana; Sia, Kian C.; Newman, Jennifer P.; Guo, Chang M.; Hui, Kam M.; Lam, Paula Y. P.
Abstract : Human bone marrow‐derived mesenchymal stem cells (MSCs) have the unique ability to home toward injuries or tumor sites. We have previously shown that the tumor‐tropic property is dependent on the intrinsic expression and activity of the matrix remodeling gene, matrix metalloproteinase 1 (MMP‐1). Herein, crosstalk between MMP‐1/protease activated receptor 1 (PAR‐1) and the G‐protein coupled receptor stromal‐derived growth factor 1 (SDF‐1)/C‐X‐C chemokine receptor 4 (CXCR‐4) in facilitating cell migration was investigated. Gain‐of‐function and RNA interference (RNAi) technology were used to evaluate the interplay between the key players. The downstream effect on the tumor‐tropic migration of MSCs was investigated using modified Boyden chamber assay. Neutralizing PAR‐1 activation using monoclonal antibody and targeted knockdown of MMP‐1 using RNAi resulted in decreased expression of SDF‐1, which was not observed in control‐RNAi‐transfected cells. Over‐expression of CXCR‐4 failed to promote MSC migration; the percentage of migrated cells toward tumor cell conditioned medium was similar to the vector‐transduced and the CXCR‐4‐transduced MSCs. Furthermore, inhibition of SDF‐1/CXCR‐4 signaling using AMD3100 reduced MSC migration through the deregulation of MMP‐1 promoter activities, protein expression, and metalloproteinase activity. Collectively, our results showed that MMP‐1‐mediated MSC tumor tropism is dependent on crosstalk with the SDF‐1/CXCR‐4 axis.—Ho, I. A. W., Yulyana, Y., Sia, K. C., Newman, J. P., Guo, C. M., Hui, K. M., Lam, P. Y. P., Matrix metalloproteinase‐1‐mediated mesenchymal stem cell tumor tropism is dependent on crosstalk with stromal derived growth factor 1/C‐X‐C chemokine receptor 4 axis. FASEB J. 28, 4359–4368 (2014). www.fasebj.org